Shotgun cloning, characterization and detection of virulence gene of staphylococcus aureus strain 125 - Abdulla, M.A.; Al-Bayaty, F.H.; Ismail, S.; Diong, S.H.; Ali, N.A.W.; Jamil, M.M.; Talaei, S.; Golbabapour, S. (Societe de Physique et d'Histoire Naturelle de Geneve, 2012)
Staphylococcus aureus is a flexible bacterium. About 20% of healthy persons are persistent carriers of Staphylococcus aureus and 60% are intermittent carriers. It expresses a wide variety of virulence factors and causes infections and diseases that range from benign skin infections to potentially fatal systemic disorders. Molecular biology has lead to unraveling of the pathogenesis of Staphylococcal diseases and identification of several virulence genes like agr, sar, nagD, and cvf genes. In this study, a shotgun cloning technique was carried out to contract the genomic library of Staphylococcus aureus strains 125(SA125), in order to screen the virulence gene in mice. SA125 is a non MRAS hospitalized strain isolated from UMMC patients. The shotgun cloning of SA125 was carried out by using Puc18 plasmid as vector and E.coli (JM109) as host. Female ICR mice (6-8 week old) were used as animal models form preliminary virulence gene screening. Beside that, recombinant plasmids screening were carried out to analyze the DNA insert. From shotgun cloning, a total of 86 recombinants clones were obtained and the inserted fragments of SA125 were in the range of 1.8-3.3kb. Seven randomly selected recombinant clones were screened for virulence gene in mice and it was revealed that SHV2 is the most virulence recombinant clone. Further studies are required to analyses and characterize the possible virulence gene of SHV2.